Analysis on Stress-Strain Model of Unsaturated Ice-Containing Soil. (16th August 2022) - Han, Qiang; Wang, Zhiguo; Teng, Zhenchao; Zhang, Yunfeng; Xue, Meng; Qin, Xiaokai
Abstract : The relationship between the stress-strain characteristics of ice-containing unsaturated soil and its various physical properties has important implications for the design and construction of transportation and building projects. The study also reveals the varying phases of the substance that can be deposited within the pore space. During winter, the freezing-thawing cycles affect the various media that can be deposited within the soil pore space, such as water and other water. The presence of water and others in the soil's pores can cause a freeze-thawing phenomenon and a significant change in the material's elastic modulus. This paper presents a method that uses the representative elementary volume (REV) model to perform a representative state variable analysis on an unsaturated ice-containing soil with porosity. The three stress-strain REV models that were developed for the study were designed to analyze the properties of an unsaturated ice-containing soil under freezing-thawing conditions. Then a comprehensive analysis of the soil's various components was performed. The effects of frozen soil on the change law of the relationship between different porous medium are studied. The study also explores the effects of the presence of porosity on the variation law of the frozen soil relationship between the stress-strain. The paper presents the study of the variation characteristics of the elastic modulus of permafrost soil. It also explores the various factors (porosity, moisture content, ice percentage, and tortuosity) that influence the stress-strain characteristics of unsaturated soil.